Questions, Perspectives and Final Considerations of Planting Native Species Under the Climate Change Conditioning - Pastorino, Mario Juan; Marchelli, Paula; Arana, María Veronica; Aparicio, Alejandro Gabriel (Springer, 2021)
There is a growing interest in Argentina (and in the world) for planting native tree species. This has triggered the development of domestication programs for those species with greater productive potential or a key ecological value. Domestication involves the development of technologies to bring wild species to plantation on an industrial scale, for commercial purposes or for the restoration of ecosystems, involving all stages of the biological/productive cycle. Knowledge is needed for industrial production of seedlings, methods and designs of plantation, intermediate silvicultural treatments, and the definition of rotation periods and adjustment of harvesting practices. As well, it also includes a perhaps inconspicuous but essential stage that predates all of these: the choice of genetic material to be reproduced.